2008
DOI: 10.1007/s00109-007-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of miR-126*, an intronic product of the vascular endothelial EGF-like 7 gene, regulates prostein translation and invasiveness of prostate cancer LNCaP cells

Abstract: MicroRNAs (miRNAs) are endogenous noncoding RNAs that down-regulate gene expression by promoting cleavage or translational arrest of target mRNAs. While most miRNAs are transcribed from their own dedicated genes, some map to introns of 'host' transcripts, the biological significance of which remains unknown. Here, we show that prostate cells are naturally devoid of EGF-like domain 7 (Egfl7) transcripts and hence also deficient in a miRNA, miR-126*, generated from splicing and processing of its ninth intron. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 46 publications
6
98
1
1
Order By: Relevance
“…Also, it has been reported that the increase in the prostein protein expression in prostate cells was due to the absence of miR-126* found in Egfl -7 gene (36). In a non-small cell lung cancer (NSCLC) study, a signifi cant reduction in CRK protein which is the functional target of miR-126 was observed while cells were transfected with pre-miR-126 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been reported that the increase in the prostein protein expression in prostate cells was due to the absence of miR-126* found in Egfl -7 gene (36). In a non-small cell lung cancer (NSCLC) study, a signifi cant reduction in CRK protein which is the functional target of miR-126 was observed while cells were transfected with pre-miR-126 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also demonstrated that miR-126 has roles in regulating adhesion molecule expression (Harris et al, 2008), providing additional control of vascular inflammation (Harris et al, 2008), regulating the VEGF/PI3K/AKT signaling pathway (Hu et al, 2010), regulating the translation and invasiveness of vascular endothelial cell sprouting (Musiyenko et al, 2008), and governing the integrity and angiogenesis of the vasculature (Kuhnert et al, 2008;Wang et al, 2008b). Using MTT assays, our research showed that the SR of Siha-miR-126 mimic was significantly reduced compared to that of control cells and that the differences between the 2 cell groups increased over time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we were able to unambiguously annotate the miRNA* strand of miRNAs such as miR-423 and miR-371. Other recent miRNA profiling efforts have found differentially expressed miRNA*s, such as miR-9*, 39 miR-199*, 40,41 miR-126*, 42,43 miR-363*, 44 miR-18*, 45 miR-29c*, 46 and miR-155*, 47 in the pathogenesis of Waldenström macroglobulinemia, lung cancer, and a metastasis model, as well as in developmental processes such as organ adhesion, respectively. In our libraries, hsa-miR-199 showed features of an ␣-duplex, whereas hsa-miR-9 and hsa-miR-363 displayed a more balanced expression (supplemental Table 2).…”
Section: Discussionmentioning
confidence: 99%